(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
In today’s global world, the importance of English cannotbe denied and ignored since English is the most common language spokeneverywhere. With the help of developing technology, English has been playing amajor role in many sectors including medicine, engineering, and education,which, in my opinion, is the most important arena where English is needed.Particularly, as a developing country, Turkey needs to make use of thisworld-wide spoken language in order to prove its international power. This can merelybe based on the efficiency of tertiary education. Consequently, English shouldbe the medium of instruction at universities in Turkey for the following threereasons: finding a high-quality job, communicating with the internationalworld, and accessing scientific sources in the student’s major field.